The German day-care study: multicomponent non-drug therapy for people with cognitive impairment in day-care centres supplemented with caregiver counselling (DeTaMAKS) - study protocol of a cluster-randomised controlled trial - Elisa-Marie Behrndt; Melanie Straubmeier; Hildegard Seidl; Stephanie Book; Elmar Graessel; Katharina Luttenberger (BMC, 2017)
Abstract Background It is the wish of both people with cognitive impairment and their informal caregivers for the impaired person to live at home for as long as possible. This is also in line with economic arguments about health. The existing structure of day-care services for the elderly can be used to achieve this. Due to the current lack of empirical evidence in this field, most day-care centres do not offer a scientifically evaluated, structured intervention, but instead offer a mixture of individual activities whose efficacy has not yet been established. Informal caregivers of people with dementia use day-care centres primarily to relieve themselves of their care tasks and as a support service. Methods/design The present study therefore investigates the effectiveness of a combination of a multicomponent activation therapy for people with mild cognitive impairment (MCI) or mild to moderate dementia at day-care centres and a brief telephone intervention for their informal caregivers. The study is conducted as a cluster-randomised intervention trial at 34 day-care centres in Germany with a 6-month treatment phase. The centres in the waitlist control group provide "care as usual". A power analysis indicated that 346 people should initially be included in the study. The primary endpoints of the study include the ability to perform activities of daily living (ADL) and cognitive capacities on the side of the day-care centre users and the subjectively perceived burden and well-being of the informal caregivers. The total duration of the study is 3 years, during which data are collected both by the psychometric testing of the people with cognitive impairment and by telephone interviews with informal caregivers. Discussion The project has three distinctive quality features. First, it is embedded in real care situations since the day-care services have already been established for this target group. Second, due to the large number of cases and the fact that the participating day-care centres are spread across the entire country, the results can be expected to be generalisable. Third, the interventions can be assumed to be implementable as they required only a one-day training event for the staff already working at the centres. Trial registration ISRCTN16412551 (Registration date: 30 July 2014, registered retrospectively).